Tobacco Industry Interference Index: Implementation of the World Health Organization's Framework Convention on Tobacco Control Article 5.3 in India. (May 2020) - Chugh, Aastha; Bassi, Shalini; Nazar, Gaurang P.; Bhojani, Upendra; Alexander, Cyril; Lal, Pranay; Gupta, Prakash C.; Arora, Monika
In India, there has been no attempt to measure the implementation of World Health Organization's Framework Convention on Tobacco Control Article 5.3, which provides guidelines to address tobacco industry interference (TII). This study draws on a desk review conducted to assess the frequency and severity of TIIs and the government's response, reported between January and December 2017. This study highlights that the government of India does not allow tobacco industry to participate in policy development. However, the industry interferes by collaborating with the government's allied organizations. The tobacco industry has diversified as food industry in India, and directly or indirectly supports various government programs, by investing through their corporate social responsibility schemes. In addition, there are limited legislative measures to allow transparency in adoption of Article 5.3 guidelines across the country. Hence, the findings of this study underscore an exigent need to adopt and implement Article 5.3 at the national level in India.